Karakteristik Kimia dan Sensori Kulit Pie Berbahan Dasar Tepung Mocaf (Modified Cassava Flour) dan Tepung Kepala Ikan Lele Dumbo (Clarias gariepinus) - Noli Novidahlia; Cici Fitriani; Distya Riski Hapsari (Universitas Djuanda, 2023)
Pie is processed food products consisting of pie crust dough and filling. A good pie crust is crispy and crumbs but not easily to crumble. In this research, pie crust were made using mocaf flour and catfish dumbo head flour. The purpose of this research was to study the effect of mocaf flour and catfish dumbo head flour substitution on physicochemical and sensory pie crust. The method used was analysis of variance (RAL) with one factor that is the ratio betwn mocaf flour and catfish dumbo head flour with four treatment levels, 100:0, 95:5, 90:10, and 85:15. The product analysis included sensory tests (sensory and hedonic quality) and chemical tests (moisture content, protein content, and calcium content). The result showed that pie crust with treatment mocaf 5%: catfish head flour 15% produced a product with good chemical composition and sensory quality.